Essays in corporate finance - Mahmud, Syed Ehsan (2018)
This thesis comprises three essays in corporate finance, with a focus on corporate risk management and debt diversity. The first chapter examines the impact of derivatives use on the cost of equity for German non-financial firms. Using hand-collected data on derivatives use for a sample of German non-financial firms, I find that user firms have a 306 basis point lower cost of equity than non-users. This reduction in the cost of equity of users is attributable to their lower market, size, and value risk factor exposures. The observed negative relation between derivatives use and the cost of equity remains robust to specifications that account for potential endogeneity arising from a firm's derivatives hedging and capital structure decisions. I find that the reduction in the cost of equity is largest for smaller firms and for firms making use of foreign currency and interest rate derivatives. Moreover, new derivatives users experience a significant reduction in the cost of equity capital in the first year of adoption.